Regional development banks, a study of institutional style - White, John Alexander; African Development Bank (London : Overseas Development Institute, 1970)
The demand of the poor countries for institutions more4 responsive to their own aspiration, essentially a political demand, is the central theme of regional development banks. The study analyses the origins, structures and evolution of the three institutions, within a comparative framework designed to show why they responded differently in a demand which in each case was expressed in more or less similar terms.
Includes bibliographical references.
usc 17/05/2017
Loans
Keywords: Inter-American Development Bank